The Performance Evaluation of Lightweight Concrete Piles on UTHM's Soft Soil under Static and Dynamic Loading Tests - Agus, S.; Ismail, B.; Amir Khan, S. (International Journal of Integrated Engineering, 2022)
Light-weight concrete generally has low density and low strength compared with normalconcrete, the use of the lightweight concrete for piling is still very rare due to high porosityand underestimate the strength. This research was done to find out the performance of lightweight concrete piles (LCP’s) which were made by Palm Oil Clinker (POC) and FoamedConcrete (FC) and to compare their performance with normal concrete pile (NC).Conventional static load test (slow maintained load test, SM) using kenteledge system toobtain pile capacities were performed for those three type of piles (NC, POC and FC)embedded in soft soil at RECESS, UTHM, Batu Pahat. Performance of piles were alsoevaluated using Pile Driving Analyzer (PDA) in dynamic loading. The results shows closecorrelation between static and dynamic test results and the stresses of compression and tensileunder both loadings were within the allowable limit state thus, the application of LCP’s fordeep foundation on soft soil is feasible.